Perancangan Struktur Menara Turbin Angin Savonius Tipe-L Untuk Pembangkit Listrik Pada Rumah Tinggal - Renalldy Djodjobo; Stenly Tangkuman; Irvan Rondonuwu (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
The tower structure of a wind power plant must be able to support other parts such as wind turbines, gearboxes and alternators. Thus the tower structure must be designed to be strong to withstand the heavy loads of other components and more specifically wind loads that can bend or break the tower structure if it is not strong enough.The purpose of this research is to calculate the load on the tower and design the tower structure for the L-type savonius wind turbine. Next, make a miniature tower to complete the miniature wind power plant which is the object of research.The tower structure is designed using pipes with dimensions; 2500 mm high, 203.20 mm outside diameter, 183.2 mm inside diameter, and 10 mm thick. The gearbox holder is made of 50 mm x 50 mm hollow steel with a thickness of 1.8 mm. The results of the static simulation of the tower structure using Solidworks 2016 show that the maximum von Mises stress is 1.33 MPa, and the maximum displacement is 1.84 mm.The designed tower is implemented in a miniature with a scale of 1:5, has a height of 50 cm and a pipe diameter of 2 inches, the gearbox holder is made of S 45 C strip steel with a size of 17 cm x 5 cm and a thickness of 5 mm.Â Keywords: PLTB, L-type savonius wind tower structure, Static simulation